2016
DOI: 10.1371/journal.pone.0166711
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Selected Populations for HIV-1 Vaccine Cohort Development in Nigeria

Abstract: Development of a globally effective HIV-1 vaccine will need to encompass Nigeria, one of the hardest hit areas, with an estimated 3.2 million people living with HIV. This cross-sectional Institutional Review Board (IRB) approved study was conducted in 2009–12 at four market sites and two highway settlements sites in Nigeria to identify and characterize populations at high risk for HIV; engage support of local stakeholders; and assess the level of interest in future vaccine studies. Demographic, HIV risk data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In this evaluation of HIV-1 genetic diversity in southwest Nigeria, we found the most common variants to be CRF02_AG and subtype G, which is similar to what previous studies examining genetic diversity in Nigeria have found [7,8,10,11,34] The dominant spread of CRF02_AG in West Africa has been attributed to the replicative fitness it confers over subtype A and G in the same geographical region [35]. The other subtypes, including D, J, K, CRF43_02G, CRF06_cpx and CRF36_cpx, which were also found in this study have also been reported in other West African settings, largely at a lower prevalence [36].…”
Section: Discussionsupporting
confidence: 88%
“…In this evaluation of HIV-1 genetic diversity in southwest Nigeria, we found the most common variants to be CRF02_AG and subtype G, which is similar to what previous studies examining genetic diversity in Nigeria have found [7,8,10,11,34] The dominant spread of CRF02_AG in West Africa has been attributed to the replicative fitness it confers over subtype A and G in the same geographical region [35]. The other subtypes, including D, J, K, CRF43_02G, CRF06_cpx and CRF36_cpx, which were also found in this study have also been reported in other West African settings, largely at a lower prevalence [36].…”
Section: Discussionsupporting
confidence: 88%
“…have been previously characterized in the country. 7 Several HIV-1 high-risk groups such as commercial sex workers, 8,9 voluntary blood donors, 10,11 long-distance drivers, [12][13][14] mammy markets contiguous to military facilities, 15 etc., have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…have been characterized in the country previously 6 . Several HIV-1 high risk groups such as commercial sex workers 7,8 , voluntary blood donors 9,10 , long distance drivers 1113 , mammy markets contiguous to military facilities 14 etc. have also been identified.…”
Section: Introductionmentioning
confidence: 99%